Electromagnetic pollution maps as a resource for assessing the risk of emissions from mobile communications antennas - Yeison Alberto Garces-Gomez; Vladimir Henao-Cespedes; Luis Fernando Diaz-Cadavid (Institute of Advanced Engineering and Science, 2020)
Electromagnetic pollution has taken on importance in recent decades, as interest is growing in knowing how the proliferation of mobile communication devices can affect the environment and generate health problems in the population. In this document, a systematic review of the methodologies for measuring electromagnetic radiation is carried out with a view to generating pollution profiles. It also develops a novel methodology for measuring electromagnetic pollution (EMP) in urban areas, and is validated with a case study using a map of EMP in the city of Manizales (Colombia), determining the spatial distribution of radiation levels. In order to generate the map, EMP measurements were carried out in the bands of local mobile telephone operators, in addition to the LPWAN (low power wide area network) LoRaWAN and Sigfox networks, Wi-Fi, and those related to IoT technologies.